Varicella infection in a non-universally vaccinated population: Actual epidemiology in Bulgaria (2013-2015) - Tatina T. Todorova (Elsevier, 2018)
Background: Varicella is a common and usually mild disease but it has great importance in regard to general infectious morbidity. The current study aimed to characterize possible risk factors of varicella epidemiology in Bulgaria, a country where infection follows its natural epidemiological pattern as no mandatory or recommended vaccine is currently applied. Methods: Administrative regions of Bulgaria were used as units of observation and a set of sociodemographic and economic determinants, as well as geographic location (south or north) were tested for associations with the mean 3-year varicella incidence rates (2013-2015). Results: The proportion of urban population, proportion of females, number of health care units and proportion of urban population aged <10 years were the four sociodemographic variables most strongly and significantly correlated (p < 0.05) with varicella frequency (Spearman's rank correlation coefficients of 0.62, 0.47, 0.43, and 0.38, respectively). After reducing the number of intercorrelated factors to a few principal components and accounting for confounders, the demographic component and geographic location remained most robustly associated with varicella incidence in Bulgaria (adjusted R2 of 0.51, p < 0.001). Conclusions: The results obtained identify important determinants in the local epidemiology of varicella and show that community characteristics should be considered, to improve our understanding of varicella distribution. Keywords: Chickenpox, Epidemiology, Notifiable infectious diseases, Varicella zoster virus, Vaccine-preventable diseases